The significance of MRI-detected lateral lymph node metastasis in rectal cancer on local recurrence and survival-A nationwide cohort study - Agger, Erik ; 0000-0003-4463-2336; Dahlbäck, Cecilia; Delorme, Cedric; Buchwald, Pamela (Colorectal Disease, 2026)
AIM: This retrospective observational cohort study aimed to investigate the prevalence of suspected lateral lymph node metastases (LLNM), as diagnosed by magnetic resonance imaging (MRI), and its impact on local recurrence (LR) and overall survival (OS). Patients who underwent dissection of suspected lymph nodes were evaluated in subgroup analysis. METHOD: Patients diagnosed with rectal cancer in Sweden between 2017 and 2021 were identified through the Swedish colorectal cancer registry and grouped by MRI findings. Main outcome measures were LR at 3 years and OS at 3 and 5 years. RESULTS: In all, 2779 patients were analysed. Frequency of lateral lymph node (LLN) enlargement on MRI was 9.4%. In univariable analysis, the risk of LR at 3 years was increased in LLN-positive patients, HR 2.79 (CI 1.55-5.03). In multivariable analysis, adjusted for patient, tumour and neoadjuvant treatment factors, this difference remained (HR 1.97 (CI 1.04-3.73)). No difference in 3-year OS was observed. At 5 years, univariable analysis indicated increased mortality in LLN-positive patients (HR 1.64 (CI 1.24-2.17)), but not in multivariable analysis. Among LLN-positive patients, those who had undergone LLN dissection (LLND) had an LR rate of 12.5% and increased risk at 3 years in univariable analysis (HR 3.73 (CI 1.93-10.76)). However, in multivariable analysis, there was no difference in LR risk or OS. CONCLUSION: MRI-detected LLN positivity is associated with a higher risk of LR and correlates with other adverse prognostic factors. The effect of LLND on LR remains unclear. Further research is needed to optimize treatment strategies for patients with suspected LLNM.
© 2026 The Author(s). Colorectal Disease published by John Wiley & Sons Ltd on behalf of Association of Coloproctology of Great Britain and Ireland.
Keywords: Humans; Rectal Neoplasms/mortality; Female; Male; Lymphatic Metastasis/diagnostic imaging; Magnetic Resonance Imaging/methods; Aged; Middle Aged; Neoplasm Recurrence, Local/mortality; Retrospective Studies; Sweden/epidemiology; Lymph Nodes/diagnostic imaging; Lymph Node Excision; Registries; Aged, 80 and over; Adult